From entry to elite: The relative age effect in the Australian football talent pathway. Issue 6 (June 2019) - Tribolet, Rhys; Watsford, Mark L.; Coutts, Aaron J.; Smith, Chris; Fransen, Job
Abstract: Objectives: This study aimed to assess the first instance and prevalence of the Relative Age Effect (RAE) in the male Australian Football (AF) talent development pathway through to the Australian Football League (AFL). Design: Retrospective cross-sectional analysis. Methods: Birthdate distribution was accessed from an U10–U12 AF academy trial (n = 514), U13–U19 AF academy players (n = 408), AFL state, national and international combines (n = 2989), AFL Rising Star nominees (n = 50) and the top ten AFL Brownlow vote recipients (n = 50) between 2013–2017. Results: Chi-squared analysis showed significant overrepresentation to early born players in the selection year for both quartile and half-year compared to the previously known distribution at different stages of the talent pathway. Odds ratio demonstrated bias to players born in quartiles one and two of the selection year compared to players born in quartile four in every cohort examined. Conclusions: RAEs appear between ages 10–12 in the male AF development pathway and continue to senior professional competition. RAEs are amplified as the competition for positions increases and at points where selection cut-offs occur. Interestingly, players receiving votes for the AFL's best and fairest award were 12.6 times more likely to be born in the first half of the year. This may suggest a latent effect, which has long term benefits for relatively older players. Nonetheless, the RAE affects career progression in a male AF talent pathway.